Dimensionamento de redes ópticas dinâmicas para data-grid service - Maioli, Celio Proliciano (2007)
WDM networks are already seen as the solution for large amount of data exchanging in data grids. This work investigates whether the use of slower (and less expensive) transponders is able to offer the same amount of service that a reference optical network by exploiting the WDM domain. In order to provide this study with more realistic traffic scenarios, we have developed a traffic monitor and an all optical network simulator. Results show the viability of equivalent service levels with economy of transponder due to spatial reuse of lightpaths. Moreover, the average number of hops is reduced, which points out to less reconfiguration efforts from the control plane standpoint with reduced overhead for clients. However, slow transponders also means longer service time and increased lightpath holding time. In other to address this issue, multiple streams associated with alternative routing are investigated but improvements, as expected, are only found mesh networks.